Аналіз практик корпоративної соціальної відповідальності вітчизняних виробничих фармацевтичних підприємств - Городецька, І. Я.; Левицька, О. Р; Ткаченко, Наталя Олександрівна; Horodetska, I. Ya.; Levytska, O. R.; Tkachenko, N. O (My University, 2023)
Subjects of the domestic pharmaceutical business consistently implement the principles of corporate social responsibility to society. The source of studying the level of social activity of domestic pharmaceutical manufacturing, wholesale enterprises and chain pharmacies is often the information content of their official websites regarding corporate social responsibility. Since the pharmaceutical business environment and the needs of society are quite dynamic, research in this direction is permanently relevant. In addition, the Russian-Ukrainian war in 2022 significantly affected the activities of all subjects of the pharmaceutical market of Ukraine, and pharmaceutical enterprises (PEs) began to implement wartime social responsibility programs. Aim. Study of the state of application of corporate social responsibility strategies of manufacturing PhE, which were among the top-20 marketing organizations in terms of the volume of pharmacy sales of medicines in 2022, in relation to individual components of social responsibility aimed at the external environment of PhE. Materials and methods. The objects of the study were information from the official websites of domestic manufacturing companies, which were among the top 20 marketing organizations in terms of the volume of pharmacy sales of medicinal products in 2022 (JSC "Farmak", PrJSC "Pharmaceutical Firm "Darnytsia", Corporation Arterium, JSC “Kyiv Vitamin Plant”, LTD "Cusum Pharm", LTD "Pharmaceutical company "Zdorovya", LTD "Yuriya-Pharm", ALC "Interchem", and PJSC “Scientific Industrial Centre “Borshchagiv Chemical and Pharmaceutical Plant”) regarding projects aimed at the external environment of Pes. The work uses the methods of information search, content analysis, systematization, comparison and generalization. Results and discussion. The vast majority of the leading domestic production enterprises have a section on social responsibility on their official websites (7 out of 9 sites), but only 2 enterprises display it on the main page of the site – JSC “Farmak” and Arterium Corporation. On the websites of 5 other PEs, it is located in the "About the company" or "About us" sections. Some of the studied PEs provide information about individual measures of social orientation in other sections of the site. For example, some PEs duplicate information about social responsibility measures in management reports and news (JSC "Farmak"), others provide such information only in management reports (JSC "Kyiv Vitamin Plant"), and still others – only in news (LTD "Cusum Pharm"). Information is structured and systematized in 5 PEs, relevant – in 6 PEs. Only three PEs (JSC "Farmak", "Arterium" Corporation, and PJSC "Borshchagiv Chemical and Pharmaceutical Plant") publish reports on corporate social responsibility. Most of the investigated PEs prepare a consolidated report or a management report. However, the information mentioned in the above reports and related to the environmental and social aspects of the PEs activities is a mandatory element established by law for responsible business. Therefore, it is advisable for domestic manufacturing companies to more actively implement practices of corporate social responsibility, which are aimed at the external environment of the Pes. Conclusion. The conducted comparison of the corporate social responsibility practices of domestic manufacturing 74PEs, which were among the top-20 marketing organizations by the volume of pharmacy sales of medicines in 2022, showed that PhEs use different criteria and different approaches in covering their social activities aimed at the external environment, which makes it difficult for society and stakeholders to compare their contribution
Analysis of corporate social responsibility practices of domestic manufacturing pharmaceutical enterprises
Keywords: pharmaceutical enterprise; social responsibility; social practices; social reporting; information content of the site